Recent advances in the development of defective black TiO2 nanomaterials for application in energy and environmental sustainability: A review - Ntakadzeni Madima; Nyiko M. Chauke; Siphelo Ngqoloda; Olga K. Mmelesi; Mpfunzeni Raphulu (Results in Engineering)
The energy crisis and environmental water pollution have become two of the most significant barriers to social and economic development owing to the rapid growth of industry and civilization. Consequently, it is vital to urgently seek out alternative energy solutions and implement strategies to mitigate water pollution. Over the years, catalysis-based technologies have been extensively researched to address energy and environmental challenges. Among a variety of catalysts employed, titanium dioxide (TiO2) stands out as the most notable catalyst that has garnered considerable attention in tackling the issues mentioned above. However, due to its wide energy bandgap, the photocatalytic efficiency of TiO2 is confined to the ultraviolet (UV) region of the spectrum. Subsequently, an effective approach to enhance the utilization of TiO2 as a catalyst is to extend its light absorption into the visible spectrum. Additionally, pure TiO2 exhibits low electrical conductivity, which restricts its practical application in energy fields. In the past decade, defective black TiO2 has emerged as an effective catalyst due to its broader light response range in both visible and even near-infrared regions, as well as its improved conductivity. Therefore, this paper briefly reviews the advancements in defective black TiO2-based catalysts aimed at addressing the energy crisis and environmental water pollution. The purpose of this review is to provide an up-to-date overview and encourage further research in this relevant field by focusing on the properties, synthesis, and application of defective black TiO2-based catalysts.